Optimization of pasteurization of meat products using pasteurization values (p-values). Issue 1 (October 2021) - Raseta, M; Jovanovic, J; Becskei, Z; Brankovic Lazic, I; Mrdovic, B; Djordjevic, V
Abstract: This study aimed to examine the effect of shortening the effective heat treatment time by 15 minutes for finely and coarsely chopped sausages and canned meat in pieces packed in polyamide casings with diameters of 75 and 90 mm. Product safety was ensured in accordance with legislation and with the producer food safety system. Optimization led to a decrease in p-values for finely chopped sausages (diameter 90: 148.8 → 97.64 minutes; diameter 75: 111.2 → 58.4 min), coarsely chopped cooked sausages (diameter 90: 115.5 → 79.1 min; diameter 75: 245.3 → 106.6 min) and for canned meat in pieces (diameter 90: 249.7 → 95.91; diameter 75: 213.9 → 48.42 min). The use of p-value in optimization confirms the pasteurization level and ensures the safety of the product in the defined storage conditions. It is also possible to compare the levels of heat treatment for different products that are differently packaged.